Evangelicals and electoral politics in Latin America: a kingdom of this world - Boas, Taylor C. (Cambridge studies in social theory, religion and politics, 2023)
"This book will appeal to faculty, graduate students, and undergraduates in political science, sociology, Latin American studies, religious studies, theology, and history. It analyses six Latin American countries over more than a century, examining the historical struggle for religious equality and contemporary battles over abortion and LGBTQ rights"--